Advancing sustainability through digital transformation: Empirical evidence from Southeast Asian listed companies - Atchara Leeraphong; Suranai Chuairuang; Supattana Sukrat (Business Strategy & Development, 2025)
Increasing awareness of sustainability issues, together with ever‐changing technological disruption, has led enterprises, especially in emerging markets, to invest more in digital technologies to enhance their sustainable competitiveness in the market. Relying on 163 firm‐year observations covering the years 2019–2023 from Indonesia, Malaysia, and Thailand, we explore the effects of digital transformation (DT) on the corporate sustainability performance. Our findings support resource‐based view theory , suggesting the adoption of digital technology by firms primarily drives their sustainability performance, particularly in environmental and social domains. To ensure the robustness of our main findings, we perform several robust tests, including the 2SLS IV method, panel fixed‐effect regression, and quantile regression. The practical implications of our findings highlight the importance for both listed companies and regulators in developing corporate and national digital strategies aimed at improving the corporate sustainability performance of the country.
Keywords: Digital transformation; Corporate sustainability; Southeast Asian companies